WHEY PROTEIN AS A HIGH-VALUE BYPRODUCT: CONSUMPTION HABITS (REMUNOM, 2026)
The present study aimed to investigate the consumption habits of Whey Protein among individuals from different age groups and educational levels. Whey Protein, a protein supplement derived from milk whey, stands out for its nutritional benefits and is widely used by individuals who engage in physical activities as well as by those seeking to improve performance, body aesthetics, and overall health. The research is characterized as descriptive, with a qualitative-quantitative approach, and the data were collected through an online questionnaire distributed via the social network Instagram. The sample consisted of 232 participants, of whom 45.7% reported having consumed or currently consuming the supplement, with the primary motivation being muscle mass gain. The study also identified diversity in consumption methods, highlighting intake diluted in milk (53.8%) and water (47.8%), as well as mixed with fruits (29.2%) and yogurt (25.5%). The results provide insights into consumer behavior, revealing a disconnect between the high consumption rate (45.7%) and the low level of technical knowledge regarding the supplement’s origin and composition. These findings may contribute to the development of more effective communication and marketing strategies by the Whey Protein industry. It is concluded that Whey Protein consumption is part of the routine of a large proportion of participants, mainly driven by aesthetic and physical performance goals, reinforcing the relevance of this topic for the production sector and for future research.